A New Harmonic Polyhedral Structure Based in Life and Well-Being as Framework to Solve the Main Problem of the Sustainable Development - Chica-Urzola, Juan Ángel; Serna Mendoza, Ciro Alfonso (European Journal of Sustainable Development, 2018)
Since its appearance in the 70s of the last century, Sustainable Development (SD) as a concept has had multiple definitions making this something that is considered still under construction. This situation has made the SD has become a problem of permanent discussion and multiple interpretations. As each new concept addresses a different element to develop and sustain, the variables, indicators, measurement, interpretation and improvement strategies vary, even making it impossible to reproduce the measurement of it or its inapplicability in different territories. A concept of SD based on a harmonized structure and founded on the well-being of the individual and the society in which it is immersed, becomes the key to overcome this problem that has even led to the deviation and indiscriminate use of the term "Sustainable" and of the SD itself. This concept of SD must respond to a polyhedral structure in which both the main or base plan and the fundamental or improvement axis are associated with life and well-being, which implies the undeniable and indissoluble existence of a fundamental relationship between the DS and Welfare and more in depth, between the development of the individual and social development. Keywords: Sustainable Development, Well-Being, Harmonic Polyhedral Structure